2023
DOI: 10.1093/jas/skad021
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber supplementation during the last 50 days of gestation improves the farrowing performance of gilts by modulating insulin sensitivity, gut microbiota, and placental function

Abstract: Our previous study found dietary konjac flour (KF) supplementation could improve insulin sensitivity and reproductive performance of sows, but its high price limits its application in actual production. This study aimed to investigate the effects of supplementation of a cheaper combined dietary fiber (CDF, using bamboo shoots fiber and alginate fiber to partially replace KF) from the last 50 days of gestation to parturition on farrowing performance, insulin sensitivity, gut microbiota, and placental function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In human studies, HFDFs were shown to improve insulin sensitivity and reduce the risk of diabetes because of their protective effects on gut homeostasis and chronic inflammation (13). Our and other previous studies in sows and mice have demonstrated that konjac flour, a source of HFDF, has beneficial effects on glucose metabolism and anti-inflammation during pregnancy (14)(15)(16). However, it remains unknown whether HFDF can resist high-fat diet (HFD)-induced maternal insulin resistance, inflammation, and poor pregnancy outcomes via gut-placenta axis.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In human studies, HFDFs were shown to improve insulin sensitivity and reduce the risk of diabetes because of their protective effects on gut homeostasis and chronic inflammation (13). Our and other previous studies in sows and mice have demonstrated that konjac flour, a source of HFDF, has beneficial effects on glucose metabolism and anti-inflammation during pregnancy (14)(15)(16). However, it remains unknown whether HFDF can resist high-fat diet (HFD)-induced maternal insulin resistance, inflammation, and poor pregnancy outcomes via gut-placenta axis.…”
Section: Introductionmentioning
confidence: 83%
“…Lachnospiraceae is a highly abundant member of the gut bacteria able to synthesize SCFAs by fermenting dietary polysaccharides (27)(28)(29). The HFDF used in this study is a hydrogel-like polysaccharide extracted from the tubers of the konjac plant with high microbial availability and SCFA production (14)(15)(16). Data from pregnant women demonstrated that butyrate levels in the umbilical vein serum and placenta were lower in GDMs than in non-GDMs, and butyrate levels in the umbilical vein serum and placenta were negatively correlated with placental TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also found in pigs. A high-fiber diet reduced proinflammatory markers like IL-6 and increased the anti-inflammatory markers like IL-10 in sows and piglets through promoting beneficial bacteria and the production of SCFAs ( 247 249 ). However, studies that investigated the therapeutic effects of dietary fiber in HDP and preterm birth are still lacking.…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…Excessive intake of DF is rare but is associated with impaired absorption of nutrients and diarrhea during pregnancy [147]. The use of DF supplementation in pregnancy has been demonstrated to improve insulin sensitivity, modulate the gut microbiota and metabolites, and increase placental vascular density [148]. Previous works have evidenced that DF can raise placental serotonin levels by promoting maternal serotonin synthesis in the colon and transport from the mother to the placenta [149].…”
Section: Fiber and Polyphenolsmentioning
confidence: 99%